A catalyst for producing hydrogen by electrolysis of water and its preparation method and application
By using carbon nanofiber-supported NiXY alloy catalysts in the process of electrolyzing water hydrogen production, the existing nickel-iron-based catalysts have been solved, and efficient and stable hydrogen production reactions in electrolyzing water hydrogen production are achieved, reducing production costs.
Patent Information
- Application Number
- CN202410309251.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-03-18
AI Technical Summary
The existing nickel-iron-based catalysts have slow catalytic rates and poor stability during the electrolytic hydrogen production process, which limits their widespread use in industrial applications.
Carbon nanofiber-supported NiXY alloy (where X is Fe or Co, Y is Pt, Ir or Ru, and the molar ratio of Ni, X, Y is 2-4:1:0.1-0.3) is used as a catalyst, and the stability and catalytic efficiency of the catalyst are improved through electrospinning technology and heat treatment.
It realizes efficient electrolysis of water and hydrogen production at a lower overpotential, improves the stability and reaction efficiency of the catalyst, reduces production costs, and is suitable for industrial applications.
Smart Images

Figure CN118207546B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for producing hydrogen by electrolyzing water, and a preparation method and application thereof, and belongs to the field of electrochemistry. Background Art
[0002] As a green and renewable energy with high energy density and zero emission, hydrogen energy is one of the important ways to solve the current energy crisis and environmental pollution. The electrolysis of water to produce hydrogen is simple, easy to build, and has a high energy conversion rate. It is an important choice for industrial hydrogen production. However, the electrolysis of water has certain thermodynamic barriers, high energy consumption, low production efficiency and high electricity costs in the actual production process. Therefore, the electrolysis process needs to rely on catalysts to break the thermodynamic barriers.
[0003] Currently, commercial Pt / C catalyst electrodes and IrO 2 / RuO 2 Catalyst electrodes are considered to be materials with good performance for hydrogen production by water electrolysis, but problems such as high cost and scarcity limit the large-scale development and use of such materials. Therefore, it is very important to design and synthesize non-precious metal-based catalyst materials, among which nickel-iron-based catalysts have attracted a lot of attention due to their low cost and abundant raw materials.
[0004] However, the commonly used nickel-iron-based catalysts have the problems of slow catalytic rate and poor stability. Exploring catalysts with fast catalytic rate and good stability while controlling costs has become an industry problem that needs to be solved urgently. Summary of the invention
[0005] The invention provides a catalyst for producing hydrogen by electrolyzing water. The catalyst has simple composition, good stability, high catalytic efficiency and low cost.
[0006] The present invention also provides a method for preparing a catalyst, which can prepare the above catalyst and has simple process and easy operation.
[0007] The present invention also provides an electrode, which comprises the above catalyst, so the electrode has a high hydrogen preparation rate and high stability.
[0008] The present invention also provides an electrolysis device, which comprises the above-mentioned electrode and can efficiently prepare hydrogen.
[0009] The present invention also provides a method for producing hydrogen by electrolyzing water. The method adopts the above catalyst to improve the efficiency of producing hydrogen by electrolyzing water and reduce the cost.
[0010] The invention provides a catalyst for producing hydrogen by electrolyzing water. The catalyst comprises a carbon nanofiber carrier and a NiXY alloy loaded on the carbon nanofiber carrier, wherein X is one of Fe and Co, and Y is one of Pt, Ir and Ru; and the molar ratio of Ni, X and Y is 2-4:1:0.1-0.3.
[0011] In the catalyst as described above, X is Fe, Y is Pt, and the molar ratio of Ni, X and Y is 3:1:0.1.
[0012] The catalyst as described above, wherein the mass percentage of carbon nanofibers in the catalyst is 60%-70%.
[0013] The catalyst as described above has a porosity of 20-50%.
[0014] The present invention also provides a method for preparing the catalyst as described above, comprising the following steps:
[0015] 1) dissolving a metal salt substance in an organic solvent and dispersing the mixture to obtain a mixed solution;
[0016] 2) adding PVP to the mixed solution and stirring for 12-24 hours to obtain a precursor solution;
[0017] 3) transferring the precursor solution into a syringe, setting the working voltage to 10-15 kV, setting the distance between the syringe needle and the collector to 10-15 cm, performing electrospinning to obtain a filamentous product, and drying to obtain a precursor;
[0018] 4) In H 2 / Ar atmosphere, heating to a heat treatment temperature of 450-600°C for a heat treatment time of 60-120min, and then cooling to room temperature to obtain the catalyst;
[0019] Wherein, the metal salt material includes one of a nickel source, an iron source or a cobalt source, and one of a platinum source, an iridium source, and a gold source.
[0020] In the preparation method as described above, in step 2), the PVP concentration in the precursor solution is 0.15-0.25 g / mL, and the metal ion concentration is 0.13-0.21 mmol / mL.
[0021] In the preparation method as described above, in step 4), the heat treatment temperature is 500-550° C., and the heat treatment time is 80-100 min.
[0022] The present invention also provides an electrode, comprising the catalyst as described above or a catalyst prepared by the preparation method as described above.
[0023] The present invention also provides an electrolysis device, comprising the catalyst as described above or using the electrode as described above.
[0024] The present invention also provides a method for producing hydrogen by electrolyzing water, wherein the method adopts the catalyst as described above.
[0025] The catalyst of the present invention is an alloy prepared in a specific molar ratio with carbon nanofibers loaded thereon, which can reduce the activation energy of the reaction and realize a highly efficient hydrogen production reaction by electrolysis of water at a relatively low overpotential, thereby effectively improving the efficiency of hydrogen production by electrolysis of water, and has high stability, thereby reducing the cost of the hydrogen production reaction by electrolysis of water, and is conducive to practical application.
[0026] The preparation method of the catalyst of the present invention has a short preparation process, simple process operation, and strong repeatability, which greatly saves the time cost and economic cost of catalyst preparation.
[0027] The electrode of the present invention has the above catalyst, so it can significantly improve the reaction efficiency of producing hydrogen by electrolyzing water and reduce the required energy input.
[0028] The electrolysis device of the present invention has the above-mentioned electrode, thus significantly improving the efficiency of the electrolysis process and having a higher hydrogen yield.
[0029] The method for producing hydrogen by electrolyzing water of the present invention adopts the above catalyst, so the method is efficient and convenient, and is conducive to industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the precursor with a resolution of 1 μm in Example 1 of the present invention;
[0031] Figure 2 This is a scanning electron microscope image of the precursor with a resolution of 200 nm in Example 1 of the present invention;
[0032] Figure 3 This is a transmission electron microscope image of the catalyst with a resolution of 1 μm in Example 1 of the present invention;
[0033] Figure 4 This is a transmission electron microscope image of the catalyst with a resolution of 20 nm in Example 1 of the present invention;
[0034] Figure 5 The catalyst contact angle effect diagram provided by Example 1 of the present invention and Comparative Example 1;
[0035] Figure 6 The electrode potential-current density curves of the electrodes provided in Example 1 and Comparative Example 1 of the present invention;
[0036] Figure 7 This is a time-electrode potential curve of the electrode provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The invention provides a catalyst for producing hydrogen by electrolyzing water. The catalyst comprises a carbon nanofiber carrier and a NiXY alloy loaded on the carbon nanofiber carrier, wherein X is one of Fe and Co, and Y is one of Pt, Ir and Ru; and the molar ratio of Ni, X and Y is 2-4:1:0.1-0.3.
[0039] The NiXY alloy in the present invention refers to an alloy containing three metal elements of Ni, X, and Y, for example, NiFePt alloy, NiCoPt alloy, NiFeIr alloy, NiCoIr alloy, NiFeRu alloy, and NiCoRu alloy.
[0040] The molar ratio of elements in the NiXY alloy of the present invention is 2-4:1:0.1-0.3. For example, the molar ratio includes but is not limited to 2:1:0.1, 3:1:0.1, 4:1:0.1, 2:1:0.2, 3:1:0.2, 4:1:0.2, 2:1:0.3, 3:1:0.3, 4:1:0.3 or a range consisting of any two of them.
[0041] The present invention does not limit the specific state of the carbon nanofiber carrier, which can be selected according to actual conditions. For example, the carbon nanofiber carrier can be in a hollow state or a solid state.
[0042] In one embodiment, the carbon nanofiber carrier is hollow, and the NiXY alloy is loaded on the inner and outer surfaces of the carbon nanofiber carrier.
[0043] The catalyst of the present invention uses carbon nanofiber as a carrier, and NiXY alloy is loaded on the carbon nanofiber carrier, and has high stability and catalytic efficiency. The inventors believe that, on the one hand, the carbon nanofiber carrier provides a stable supporting platform for the catalyst, thereby improving the overall stability of the catalyst; on the other hand, the carbon nanofiber carrier provides a large number of active sites, and the NiXY alloy can be evenly dispersed on the carbon nanofiber carrier, fully utilizing the catalytic activity of the alloy and improving the catalytic efficiency of the catalyst.
[0044] Furthermore, in a specific embodiment of the present invention, X is Fe, Y is Pt, and the molar ratio of Ni, X, and Y is 3:1:0.1.
[0045] Specifically, the catalyst includes a carbon nanofiber carrier and a NiFePt alloy supported on the carbon nanofiber carrier, wherein the element molar ratio of Ni, Fe and Pt is 3:1:0.1.
[0046] The inventors have found through a large number of creative experiments that when the metal element type and the molar ratio of the elements of the catalyst are within the above range, the catalyst has better stability and catalytic efficiency. The inventors believe that when the metal element type and the molar ratio of the elements of the catalyst are within the above range, the synergistic effect between the components can be better exerted, the adsorption and activation capabilities of the reactants can be improved, and the catalytic efficiency can be improved.
[0047] Furthermore, in a specific embodiment of the present invention, the mass percentage of the carbon nanofiber carrier in the catalyst is 60%-70%.
[0048] In detail, the present invention measures the mass percentage of the carbon nanofiber carrier in the catalyst by a thermogravimetric analyzer.
[0049] The mass percentage of the carbon nanofiber carrier in the catalyst includes but is not limited to 60%, 62%, 64%, 66%, 68%, 70% or any combination thereof.
[0050] The contact angle between the catalyst and water is measured by a contact angle tester. When the mass percentage of the carbon nanofiber carrier in the catalyst is within the above range, the contact angle between the catalyst and water is 76°-96°, which has high hydrophilicity. The catalyst is more likely to contact the electrolyte, which enhances the reaction efficiency and improves the chemical reaction kinetics. At the same time, when the mass percentage of the carbon nanofiber carrier is within the above range, the catalyst has good electrical conductivity, thermal stability and mechanical stability, further improving the catalytic efficiency of the catalyst.
[0051] Furthermore, in one embodiment of the present invention, the porosity of the catalyst is 20-50%.
[0052] The porosity of the catalyst in the present invention refers to the ratio of the pore volume of the catalyst to the total volume, and the pore volume of the catalyst includes external pores and internal pores.
[0053] In detail, the porosity of the catalyst of the present invention is measured by the BET method.
[0054] The porosity of the catalyst is 20-50%. For example, the porosity includes but is not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50% or any two thereof.
[0055] When the porosity of the catalyst is within the above range, it can not only increase the active sites and improve the catalytic performance, but also avoid structural changes of the catalyst during the reaction as much as possible, thereby improving the stability of the catalyst.
[0056] The present invention also provides a method for preparing the catalyst as described above, comprising the following steps:
[0057] 1) dissolving a metal salt substance in an organic solvent and dispersing the mixture to obtain a mixed solution;
[0058] 2) Add PVP to the mixed solution and stir for 12-24 hours to obtain a precursor solution;
[0059] 3) Transfer the precursor solution to a syringe, set the working voltage to 10-15 kV, set the distance between the syringe needle and the collector to 10-15 cm, perform electrospinning to obtain a filamentous product, and dry to obtain a precursor;
[0060] 4) In H 2 / Ar atmosphere, heating to a heat treatment temperature of 450-600°C for 60-120 min, and then cooling to room temperature to obtain a catalyst;
[0061] The metal salt material includes one of a nickel source, an iron source or a cobalt source, and one of a platinum source, an iridium source, and a gold source.
[0062] Specifically, in step 1), a nickel source, one of an iron source or a cobalt source, and one of a platinum source, an iridium source, and a gold source are dissolved in an organic solvent and dispersed to obtain a mixed solution.
[0063] It can be understood that when the nickel source, the iron source or the cobalt source, the platinum source, the iridium source, and the gold source are mixed, the molar ratio of the metal elements is 2-4:1:0.1-0.3.
[0064] In one embodiment, the nickel source, the iron source, and the platinum source are dispersed in an organic solvent at an element molar ratio of 3:1:0.1, and stirred until they are uniformly dispersed to obtain a mixed solution.
[0065] The present invention does not limit the specific type of the organic solvent, and the organic solvent can be selected according to actual needs; for example, the organic solvent is a composite solution of ethanol and DMF, wherein the volume ratio of ethanol to DMF is 1:5.
[0066] The present invention does not limit the specific type of metal salt substances, and common metal salt substances in the art can be selected. For example, nickel sources include but are not limited to nickel nitrate hexahydrate, nickel sulfate hexahydrate, and nickel chloride. Iron sources include but are not limited to iron nitrate nonahydrate, iron sulfate, and iron chloride. Platinum sources include but are not limited to sodium tetrachloroplatinate, diammonium tetrachloroplatinate, potassium tetrachloroplatinate, and ammonium tetrachloroplatinum. Cobalt sources include but are not limited to cobalt nitrate hexahydrate, cobalt sulfate, and cobalt chloride hexahydrate. Iridium sources include but are not limited to iridium nitrate, iridium sulfate, and iridium chloride. Ruthenium sources include but are not limited to ruthenium chloride and ruthenium nitrate.
[0067] It is understood that the metal salt substance and the organic solvent can be fully mixed by stirring, and the present invention does not limit parameters such as stirring speed, as long as sufficient mixing can be achieved.
[0068] The present invention does not limit the stirring time, and a suitable time can be selected according to actual conditions.
[0069] In step 2), PVP is added to the mixed solution and stirred for 12-24 hours to allow the PVP and the mixed solution to be fully mixed to obtain a precursor solution.
[0070] The present invention does not limit parameters such as the stirring speed during step 2), and a suitable stirring speed can be selected according to actual conditions.
[0071] In step 3), the precursor solution is transferred to a syringe, the working voltage is set to 10-15 kV, the distance between the syringe needle and the collector is 10-15 cm, the precursor droplets at the syringe needle generate charge movement under the action of the voltage, the electrostatic repulsion of the charged precursor droplets is higher than the surface tension, and the conical droplets are ejected from the tip of the cone to form a "Taylor cone", which is finally collected in the collector to obtain a filamentous product, which is then dried to obtain a precursor.
[0072] The present invention does not limit the type of equipment used in the electrospinning step in step 3), and a common NF-500 electrospinning apparatus in the art can be used. The collector can be aluminum foil or other suitable collectors.
[0073] The present invention does not limit the pushing speed used in the electrospinning step in step 3), and a suitable pushing speed can be selected according to actual needs, for example, 0.5-1.0 mL / h.
[0074] When drying the filamentous product, a suitable temperature and time can be selected according to the actual situation. For example, in a specific implementation process, the temperature is 100° C. and vacuum drying is performed for 24 hours to obtain a precursor.
[0075] In step 4), in H 2 / Ar atmosphere, heating to a heat treatment temperature of 450-600°C for 60-120 min, and then cooling to room temperature to obtain a catalyst.
[0076] The present invention does not limit the type of equipment and instruments required for step 4), and common instruments in the art, such as a tube furnace, can be selected.
[0077] The present invention does not limit the heating rate in step 4), and a suitable heating rate may be selected according to actual conditions, for example, 1-2°C / min.
[0078] The preparation method provided by the present invention combines electrostatic spinning technology with temperature reduction, and prepares a catalyst by selecting specific electrostatic spinning parameters and the temperature of temperature reduction, wherein the catalyst comprises a carbon nanofiber carrier and an alloy supported on the carbon nanofiber carrier. The preparation method has simple process, controllable conditions and reproducibility. The catalyst prepared by the preparation method has relatively excellent stability and catalytic performance.
[0079] Furthermore, in a specific embodiment of the present invention, in step 2), the PVP concentration in the precursor solution is 0.15-0.25 g / mL, and the metal ion concentration is 0.13-0.21 mmol / mL.
[0080] In detail, the PVP concentration in the precursor solution is 0.15-0.25 g / mL. For example, the PVP concentration includes but is not limited to 0.15 g / mL, 0.16 g / mL, 0.17 g / mL, 0.18 g / mL, 0.19 g / mL, 0.20 g / mL, 0.21 g / mL, 0.22 g / mL, 0.23 g / mL, 0.24 g / mL, 0.25 g / mL or a range consisting of any two of them.
[0081] The concentration of metal ions in the precursor solution refers to the total concentration of metal types involved in the synthesis of the alloy. Taking nickel-iron-platinum alloy as an example, the concentration of metal ions refers to the sum of the concentrations of nickel ions, iron ions, and platinum ions.
[0082] In detail, the concentration of metal ions in the precursor solution is 0.13-0.21 mmol / mL. For example, the concentration of metal ions in the precursor solution includes but is not limited to 0.13 mmol / mL, 0.14 mmol / mL, 0.15 mmol / mL, 0.16 mmol / mL, 0.17 mmol / mL, 0.18 mmol / mL, 0.19 mmol / mL, 0.20 mmol / mL, 0.21 mmol / mL or a range consisting of any two of them.
[0083] It can be understood that the metal ion concentration in the precursor solution can be controlled by controlling the mass volume ratio of the metal salt substance to the organic solvent in step 1), and the PVP concentration in the precursor solution can be controlled by controlling the mass volume ratio of PVP to the organic solvent in step 2).
[0084] The inventors have found through a large number of creative experiments that when the PVP concentration and the metal ion concentration are within the above ranges, the mass percentage of carbon nanofibers in the prepared catalyst is 60%-70%, which makes the catalyst have better stability and catalytic performance.
[0085] Furthermore, in a specific embodiment of the present invention, in step 4), the heat treatment temperature is 500-550° C., and the heat treatment time is 80-100 min.
[0086] Specifically, the heat treatment temperature is 500-550°C. For example, the heat treatment temperature includes but is not limited to 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or a range consisting of any two of them.
[0087] The heat treatment time is 80-100 min. For example, the heat treatment time includes but is not limited to 80 min, 85 min, 90 min, 95 min, 100 min or a range consisting of any two of them.
[0088] When the heat treatment temperature and the heat treatment time are within the above ranges, the porosity of the prepared catalyst is 20%-50%, which can increase the specific surface area and improve the reaction rate while maintaining high stability.
[0089] The present invention also provides an electrode, comprising the catalyst as described above or a catalyst prepared by the preparation method as described above.
[0090] The catalyst in the present invention is adsorbed or coated on the surface of the negative electrode material to obtain an electrode, so as to realize an efficient hydrogen production reaction by electrolyzing water.
[0091] The present invention does not limit the specific process flow of adsorbing or coating the catalyst on the surface of the negative electrode material. For example, the catalyst is coated on the surface of the negative electrode material using a naphthol adhesive.
[0092] The present invention does not limit the specific type of negative electrode material, and common negative electrode materials in the art, such as Pt, graphite, etc., can be selected.
[0093] Since the electrode provided by the present invention includes the above catalyst, it has higher efficiency and stability in the process of producing hydrogen by electrolyzing water.
[0094] The present invention also provides an electrolysis device, comprising the catalyst as described above or using the electrode as described above.
[0095] It can be understood that the electrolysis device includes an electrolytic cell, a positive electrode, and a power supply in addition to the above-mentioned electrodes.
[0096] The electrolytic cell is used to contain water and electrolyte solution, and is usually made of corrosion-resistant materials, such as polymers or alloy materials.
[0097] The power supply is used to provide the required voltage and current, and a DC power supply or an AC power supply can be selected according to actual needs.
[0098] The electrolyte solution is used to increase the conductivity of electrolyzed water, and any electrolyte solution commonly used in the art, such as salt, alkali or acid, may be selected.
[0099] To ensure the normal operation and safety of the device, a control system can also be set up to monitor and adjust parameters such as voltage and current.
[0100] Since the electrolysis device provided by the present invention includes the above-mentioned catalyst or electrode, the electrolysis efficiency is high and the electrolysis stability is good during the process of electrolyzing water to produce hydrogen.
[0101] The present invention also provides a method for producing hydrogen by electrolyzing water, using the catalyst as described above.
[0102] Since the method provided by the present invention adopts the above-mentioned catalyst, the method can effectively improve the efficiency of hydrogen production by electrolysis of water and increase the electrolysis stability when used in the process of hydrogen production by electrolysis of water.
[0103] The catalyst, electrode and electrolysis device of the present invention are described in more detail below through specific examples.
[0104] Example 1
[0105] The preparation process of the catalyst, electrode and electrolysis device of this embodiment is as follows:
[0106] 1. Weigh 1.5mmol Ni(NO 3 ) 2 6H 2 O, 0.5mmolFe(NO 3 ) 3 9H 2 O and 0.05mmolK 2 PtCl 6 Disperse in 2 mL ethanol and 10 mL DMF solution, and stir vigorously for 30 min until the solution is evenly dispersed. Then, add 2.0 g PVP to the solution and stir for 12 h to obtain a precursor solution;
[0107] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 10 kV and the syringe needle is 10 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor. Figure 1 and Figure 2 The scanning electron microscope images obtained by scanning electron microscope detection of the precursor at different resolutions;
[0108] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , and the temperature was raised to 500°C. Then the temperature was kept constant for 90 min. 2 / Ar gas flow to room temperature to obtain a catalyst, wherein the carbon nanofiber content in the catalyst is 65% and the porosity is 35%; Figure 3 , Figure 4 These are transmission electron microscopy images of the catalyst obtained by transmission electron microscopy at different resolutions.
[0109] 4. Preparation of electrode: Weigh 5 mg of the prepared catalyst into a 5 mL centrifuge tube, use a pipette to measure 1 mL of anhydrous ethanol and add it to the centrifuge tube, sonicate in an ultrasonic machine for 20 min, add 50 μL of naphthol (Nafion) solution after the sample is dissolved, and continue sonication for 20 min to completely mix the catalyst and naphthol in ethanol to obtain a 5 mg / mL mixed solution;
[0110] Use a pipette to measure 60 μL of the mixed solution and evenly apply it on the front of a rectangular carbon paper with a thickness of 0.2 cm and a surface area of 1 cm × 3 cm. Then weigh 60 μL of the mixed solution and evenly apply it on the back of the carbon paper. Use a hair dryer to dry it to prepare the working electrode. The catalyst loading on the carbon paper is 0.2 mg / cm 2 .
[0111] 5. Assemble the electrolysis device: Use alkaline water as the electrolyte, apply voltage and the positive and negative electrodes to form a closed circuit to decompose water into hydrogen and oxygen.
[0112] Example 2
[0113] The preparation process of the catalyst in this embodiment is different from that in Embodiment 1, and the preparation process of the electrode and the electrolysis device is the same as that in Embodiment 1. The preparation process of the catalyst is as follows:
[0114] 1. Weigh 1.5mmol Ni(NO 3 ) 2 6H 2 O, 0.75mmolFe(NO3 ) 3 9H 2 O and 0.225mmolK 2 PtCl 6 Disperse in 2 mL ethanol and 10 mL DMF solution, and stir vigorously for about 30 min until the solution is evenly dispersed. Then, add 2.0 g PVP to the solution and stir for 24 h to obtain a precursor solution;
[0115] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 15 kV and the syringe needle is 15 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor;
[0116] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , the temperature was raised to 550℃, and then the temperature was kept constant for 80min. 2 / Ar gas flow to room temperature to obtain a catalyst, wherein the carbon nanofiber content in the catalyst is 60% and the porosity is 29%;
[0117] Example 3
[0118] The preparation process of the catalyst in this embodiment is different from that in Embodiment 1, and the preparation process of the electrode and the electrolysis device is the same as that in Embodiment 1. The preparation process of the catalyst is as follows:
[0119] 1. Weigh 1.5mmol Ni(NO 3 ) 2 6H 2 O, 0.75mmolCo(NO 3 ) 2 9H 2 O and 0.225mmolK 2 PtCl 6 Disperse in 2 mL ethanol and 10 mL DMF solution, and stir vigorously for about 30 min until the solution is evenly dispersed. Then, add 2.0 g PVP to the solution and stir for 20 h to obtain a precursor solution;
[0120] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 12 kV and the syringe needle is 12 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor;
[0121] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , the temperature was raised to 520℃, and then the temperature was kept constant for 100min. 2 / Ar gas flow to cool to room temperature to obtain a catalyst, wherein the carbon nanofiber content in the catalyst is 61% and the porosity is 27%.
[0122] Example 4
[0123] The preparation process of the catalyst in this embodiment is different from that in Embodiment 1, and the preparation process of the electrode and the electrolysis device is the same as that in Embodiment 1. The preparation process of the catalyst is as follows:
[0124] 1. Weigh 1.5mmol Ni(NO 3 ) 2 6H 2 O, 0.75mmolCo(NO 3 ) 2 9H 2 O and 0.225mmolIr(NO 3 ) 3 Disperse in 2 mL ethanol and 10 mL DMF solution, and stir vigorously for about 30 min until the solution is evenly dispersed. Then, add 2.0 g PVP to the solution and stir for 15 h to obtain a precursor solution;
[0125] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 12 kV and the syringe needle is 13 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor;
[0126] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , the temperature was raised to 540℃, and then the temperature was kept constant for 100min. 2 The catalyst was cooled to room temperature under a / Ar gas flow to obtain a catalyst having a carbon nanofiber content of 60% and a porosity of 27%.
[0127] Example 5
[0128] The preparation process of the catalyst in this embodiment is different from that in Embodiment 1, and the preparation process of the electrode and the electrolysis device is the same as that in Embodiment 1. The preparation process of the catalyst is as follows:
[0129] 1. Weigh 1.5mmol Ni(NO 3 ) 2 6H 2 O, 0.75mmolCo(NO 3 ) 2 9H 2 O and 0.225mmolRuCl 3 Disperse in 2 mL of ethanol and 10 mL of DMF solution, and stir vigorously for about 30 min until the solution is evenly dispersed. Then, add 2.0 g of PVP to the solution and stir for 12 h to obtain a precursor solution;
[0130] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 10 kV and the syringe needle is 12 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor;
[0131] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , the temperature was raised to 550℃, and then the temperature was kept constant for 85min. 2 / Ar gas flow to room temperature to obtain a catalyst, wherein the carbon nanofiber content in the catalyst is 61% and the porosity is 26%;
[0132] Example 6
[0133] The preparation process of the catalyst, electrode and electrolysis device in this embodiment is basically the same as that in embodiment 1, except that:
[0134] In step 1), Ni(NO 3 ) 2 6H 2 O is 1.6 mmol, Fe(NO 3 ) 3 9H 2 O is 0.4 mmol and K 2 PtCl 6 The prepared catalyst has a carbon nanofiber content of 62% and a porosity of 35%.
[0135] Example 7
[0136] The preparation process of the catalyst, electrode and electrolysis device in this embodiment is basically the same as that in embodiment 3, except that:
[0137] In step 1), Ni(NO 3 ) 2 6H 2 O is 1.6 mmol, Co(NO 3 ) 2 9H 2 O is 0.4 mmol and K 2 PtCl 6 The carbon nanofiber content in the prepared catalyst is 61% and the porosity is 35%.
[0138] Example 8
[0139] The preparation process of the catalyst, electrode and electrolysis device in this embodiment is basically the same as that in embodiment 4, except that:
[0140] In step 1), Ni(NO 3 ) 2 6H 2 O is 1.5 mmol, Co(NO 3 ) 2 9H 2 O is 0.5 mmol and Ir(NO 3 ) 3 The prepared catalyst has a carbon nanofiber content of 60% and a porosity of 35%.
[0141] Example 9
[0142] The preparation process of the catalyst, electrode and electrolysis device in this embodiment is basically the same as that in embodiment 1, except that:
[0143] In step 1), the metal ion concentration is 1.9 mmol Ni(NO 3 ) 2 6H 2 O, 0.95mmolFe(NO 3 ) 3 9H 2 O, 0.095 molK 2 PtCl 6 , PVP is 1.5g.
[0144] The prepared catalyst has a carbon nanofiber content of 54% and a porosity of 23%;
[0145] Example 10
[0146] The preparation process of the catalyst, electrode and electrolysis device in this embodiment is basically the same as that in embodiment 1, except that:
[0147] In step 3), the heat treatment temperature is 450° C. and the heat treatment time is 2 h.
[0148] The prepared catalyst has a carbon nanofiber content of 60% and a porosity of 15%;
[0149] Comparative Example 1
[0150] The catalyst preparation method of this comparative example comprises the following steps:
[0151] 1. Mix 2 mL of ethanol and 10 mL of DMF solution, then add 2.0 g of PVP to the solution and stir for 12 h to obtain a precursor solution;
[0152] 2. Transfer the precursor solution into a syringe for electrospinning, where the voltage of the electrospinning process is 10 kV and the syringe needle is 15 cm away from the aluminum foil. After the electrospinning is completed, collect the fibrous spinning product and put it into a beaker. Then, vacuum dry the spinning product at 100 ° C for 24 hours to obtain the precursor;
[0153] 3. Place the precursor in a crucible and then place it in the center of a tube furnace. Remove the air from the tube furnace and fill it with H 2 / Ar atmosphere, and the heating rate was adjusted to 1℃ min -1 , and then heated to 500℃ and kept at this temperature for 80min. 2 The reaction mixture was cooled to room temperature under an Ar flow to obtain a catalyst.
[0154] The electrodes and electrolysis device were prepared according to the method of Example 1.
[0155] Comparative Example 2
[0156] The preparation process of the electrode and the electrolysis device in this comparative example is the same as that in Example 1, but the catalyst preparation process is different, as follows:
[0157] Step 1) Ni(NO 3 ) 2 6H 2 O is 1mmol, Fe(NO 3 ) 3 9H 2 O is 1mmol and K 2 PtCl 6 It is 0.1mmol.
[0158] Comparative Example 3
[0159] The preparation process of the electrode and the electrolysis device in this comparative example is the same as that in Example 1, but the catalyst preparation process is different, as follows:
[0160] In step 1), Fe(NO 3 )3 9H 2 O is replaced by Cu(NO 3 ) 2 .
[0161] Test Case
[0162] 1. Hydrophilicity test
[0163] The hydrophilicity test was performed on the catalysts prepared in the above Examples 1-9 and Comparative Examples 1-3, and the specific steps are as follows:
[0164] Drop a drop of liquid on the solid surface, wait for the solid-liquid-gas three-phase interface to reach equilibrium, take a photo of the equilibrium system, and measure the contact angle using the contact angle measurement method provided by the software. You can also take photos or videos of the equilibrium process at regular intervals during the test, and then analyze the system change process.
[0165] The test results are shown in Table 1 and the test effect diagram is shown in Figure 5 , specifically, Figure 5 B is the hydrophilicity test effect diagram of the catalyst prepared in Example 1. Figure 5 A in the figure is a hydrophilicity test effect diagram of the catalyst prepared in Comparative Example 1.
[0166] Table 1
[0167] Serial number Contact angle (°) Example 1 76.8 Example 2 81.2 Example 3 82.3 Example 4 85.1 Example 5 85.9 Example 6 88.5 Example 7 86.4 Example 8 90.8 Example 9 97.4 Example 10 93.2 Comparative Example 1 147.3 Comparative Example 2 123.9 Comparative Example 3 118.5
[0168] 2. Electrode performance test
[0169] 1) The electrode potentials prepared in Examples 1-10 and Comparative Examples 1-3 were tested using a three-electrode system. The specific test steps are as follows:
[0170] Before use, connect the power cord and the electrodes, the red clip wire to the auxiliary electrode; the green clip wire to the working electrode; the white clip wire to the reference electrode. After the power cord and the electrodes are connected, insert the three-electrode system into the electrolytic cell for testing, and measure the electrode potential, which is recorded as V1.
[0171] The test results are shown in Table 2. Figure 6 The electrode potential-current density curves provided for Example 1 and Comparative Example 1.
[0172] 2) The activity of the electrodes prepared in Examples 1-10 and Comparative Examples 1-3 was tested using a chronopotentiometry (constant current) method. The specific test steps are as follows:
[0173] Start the electrolysis device and maintain the current density at 10 mA cm -2 After 100 hours of continuous operation, the negative electrode potential is measured and recorded as V2, and the electrode activity = V2 / V1.
[0174] The test results are shown in Table 2. Figure 7 This is a time-electrode potential curve of the electrode provided in Example 1.
[0175] Table 2
[0176] Serial number Electrode potential (mV) active(%) Example 1 105 91 Example 2 111 90 Example 3 123 88 Example 4 138 87 Example 5 152 85 Example 6 157 81 Example 7 178 79 Example 8 167 80 Example 9 181 77 Example 10 193 79 Comparative Example 1 215 75 Comparative Example 2 234 76 Comparative Example 3 249 73
[0177] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A catalyst for producing hydrogen by electrolysis of water, characterized in that: The catalyst comprises a carbon nanofiber carrier and a NiXY alloy supported on the carbon nanofiber carrier, wherein X is one of Fe and Co, and Y is one of Pt and Ir; the molar ratio of Ni, X and Y is 2-4:1:0.1-0.3; The mass percentage of carbon nanofibers in the catalyst is 60%-70%, and the contact angle between the catalyst and water is 76°-96°; The porosity of the catalyst is 20-50%.
2. The catalyst according to claim 1, characterized in that X is Fe, Y is Pt, and the molar ratio of Ni, X and Y is 3:1:0.
1.
3. A method for preparing the catalyst according to claim 1 or 2, characterized in that: The following steps are involved: 1) dissolving a metal salt substance in an organic solvent and dispersing the mixture to obtain a mixed solution; 2) adding PVP to the mixed solution and stirring for 12-24 hours to obtain a precursor solution; 3) transferring the precursor solution into a syringe, setting the working voltage to 10-15 kV, setting the distance between the needle of the syringe and the collector to 10-15 cm, performing electrospinning to obtain a filamentous product, and drying to obtain a precursor; 4) In a H2 / Ar atmosphere, the temperature is raised to a heat treatment temperature of 450-600°C for a heat treatment time of 60-120 min, and then cooled to room temperature to obtain the catalyst; Wherein, the metal salt material includes one of a nickel source, an iron source or a cobalt source, and one of a platinum source and an iridium source.
4. The preparation method according to claim 3, characterized in that: In step 2), the PVP concentration in the precursor solution is 0.15-0.25 g / mL, and the metal ion concentration is 0.13-0.21 mmol / mL.
5. The preparation method according to claim 3, characterized in that: In step 4), the heat treatment temperature is 500-550° C. and the heat treatment time is 80-100 min.
6. An electrode, characterized in that: The invention comprises the catalyst according to claim 1 or 2 or the catalyst prepared by the preparation method according to claim 3.
7. An electrolysis device, characterized in that: The catalyst comprises the catalyst according to claim 1 or 2 or the electrode according to claim 6.
8. A method for producing hydrogen by electrolysis of water, characterized in that: The method adopts the catalyst described in claim 1 or 2.
Citation Information
Patent Citations
FeCoNi-MnRu high-entropy alloy / carbon nanofiber electro-catalytic material for full-pH hydrogen evolution reaction
CN113549946A